Evaluation of Quality of Life and Surgical Outcomes for Treatment of Diverticular Disease - Lin, Mayin; Raman, Shankar R. (Clinics in Colon and Rectal Surgery, 2018)
The prevalence of diverticular disease in the Western and industrialized nations has increased over the last century, and our understanding of this disease and its management continues to evolve. In this article, we review the literature regarding the postoperative quality of life (QOL) and functional outcomes following surgical management of diverticulitis, including information regarding bowel function, recurrence of symptoms, and other postoperative sequelae. While objective parameters, such as attacks of diverticulitis, complications, and clinical episodes have been studied, there is a paucity of data on less objective factors, such as overall patient satisfaction after operative management of diverticular disease. The literature shows improvement in QOL following surgical intervention for diverticulitis if preoperative QOL was significantly low, secondary to severe/complicated diverticulitis. However, a subset of patients does continue to have symptoms following surgical intervention for diverticulitis. Often neglected in the literature, there remains a need for prospective data evaluating preoperative function to ascertain the impact of surgery on patients' QOL and postoperative function.
Keywords: diverticular disease; quality-of-life measurement; surgical outcomes; postoperative sequelae